2013
DOI: 10.1016/j.cbpa.2013.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme catalysed tandem reactions

Abstract: To transfer to the laboratory, the excellent efficiency shown by enzymes in Nature, biocatalysis, had to mimic several synthetic strategies used by the living organisms. Biosynthetic pathways are examples of tandem catalysis and may be assimilated in the biocatalysis field for the use of isolated multi-enzyme systems in the homogeneous phase. The concurrent action of several enzymes that work sequentially presents extraordinary advantages from the synthetic point of view, since it permits a reversible process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(52 citation statements)
references
References 70 publications
0
52
0
Order By: Relevance
“…The basic principle of cascade reactions is also frequently used in biocatalysis, using enzymes in isolation, as well as in combination with chemocatalysts (see Fig. 1 and Box 1 for definition of terms) [1][2][3][4][5][6][7] . As there is no need for purification and isolation of intermediates, operating time, production costs and waste are reduced, and concomitantly, overall yields are improved.…”
mentioning
confidence: 99%
“…The basic principle of cascade reactions is also frequently used in biocatalysis, using enzymes in isolation, as well as in combination with chemocatalysts (see Fig. 1 and Box 1 for definition of terms) [1][2][3][4][5][6][7] . As there is no need for purification and isolation of intermediates, operating time, production costs and waste are reduced, and concomitantly, overall yields are improved.…”
mentioning
confidence: 99%
“…Anyhow, cascade biocatalysis becomes particularly sophisticated yet appealing when redox-neutral (see Section 'Cofactor regeneration') or recycling cascades [47] are designed. A couple of excellent and comprehensive reviews on synthetic cascade reactions can be suggested to the reader [48][49][50].…”
Section: Multi-step Biocatalysismentioning
confidence: 99%
“…24 Multi-enzyme-catalyzed cascade reactions have been proposed for the synthesis of value-added chemicals including long-chain dicarboxylic acids, chiral lactones, alcohols, amines, and amino acids. 5–8 In addition, several C2–C6 platform chemicals have been successfully produced from glucose using natural or engineered microbial strains. 9 …”
Section: Introductionmentioning
confidence: 99%